1999
DOI: 10.1677/jme.0.0230153
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogens regulate pituitary alpha2,3-sialyltransferase messenger ribonucleic acid levels in the female rat

Abstract: Follicle-stimulating hormone (FSH) is synthesized by the anterior pituitary gland in multiple molecular forms. Increased acidic/sialylated FSH charge isoforms are associated with conditions characterized by a low oestrogen output. In the present study, we analysed the dynamics of the changes in mRNA levels of the enzyme Galbeta1,3[4]GlcNAc alpha2,3-sialyltransferase (2,3-STase) (one of the enzymes that incorporate sialic acid residues into the FSH molecule) in intact and ovariectomized rats. The anterior pitui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 59 publications
(62 reference statements)
1
27
0
1
Order By: Relevance
“…Similar effects have been observed after estrogen administration [23, 24]. In this regard, it has been proposed that E 2 may affect mRNA expression of the pituitary α-2,3-sialyltransferase, the enzyme responsible for the incorporation of the terminal sialic acid to the FSH carbohydrate chains [25]. In normal women, previous studies have demonstrated that the endocrine milieu modulates not only the incorporation of the terminal sialic acid to the carbohydrate chain but also the processing of the inner structure of FSH oligosaccharides [17].…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…Similar effects have been observed after estrogen administration [23, 24]. In this regard, it has been proposed that E 2 may affect mRNA expression of the pituitary α-2,3-sialyltransferase, the enzyme responsible for the incorporation of the terminal sialic acid to the FSH carbohydrate chains [25]. In normal women, previous studies have demonstrated that the endocrine milieu modulates not only the incorporation of the terminal sialic acid to the carbohydrate chain but also the processing of the inner structure of FSH oligosaccharides [17].…”
Section: Introductionmentioning
confidence: 60%
“…FSH oligosaccharide heterogeneity and its hormonal regulation have been mainly ascribed to variations in the sialic acid content of FSH glycosylation variants [12, 13, 21, 22, 23, 24, 25, 30]. However, the hormonal regulation of FSH polymorphism is exerted not only at the level of the terminal sugar residue incorporated to the carbohydrate chain, but also in the processing of the inner structure of oligosaccharides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation agrees with previous studies showing that both plasma bioactive LH concentrations and the calculated B:I LH ratio increase across male puberty [42,43], but not with studies employing monoclonal antibody-based immunoassay procedures [44,45], thus emphasizing the potential effect of differential glycosylation on the reactivity of [46][47][48][49]. The observed changes in relative in vitro bioactivity and B:I ratio of gonadotropins across puberty, may result from modifications in the carbohydrate structure of gonadotropins as documented by studies showing that both serum LH and FSH charge isoform distribution changes during early normal puberty in males [16,17], due presumably to progressive exposure to sex steroid hormones and/or GnRH [38,41,[50][51][52][53][54][55][56][57][58].…”
Section: Discussionmentioning
confidence: 99%
“…28 Pituitary expression of different glycosyl transferases, including 2,3 α-sialyltransferase (an enzyme that catalyses the incorporation of sialic acid residues into sugar residues attached to the FSH molecule), is down-regulated by estradiol. 29 Recent studies have shown that estradiol administered to postmenopausal women shifts pituitary FSH release to more basic FSH isoforms compared with non-treated women. 28 Thus, in addition to the fine-tuned interplay between the selected developing follicle and pituitary release of gonadotrophins, it appears that the follicle is capable also of directing the isoform profile released.…”
Section: Natural Fsh Isoforms and Their Physiological Relevancementioning
confidence: 99%